Assessing household food insecurity experience in the context of deforestation in Cameroon. (April 2019) - Tata Ngome, Precillia I.; Shackleton, Charlie; Degrande, Ann; Nossi, Eric Joel; Ngome, Francis
Highlights: HFIAS can be used to monitor for forest management vis-a-vis food security. The least deforested zone was least affected by food insecurity. Household FIS access deteriorates with increasing deforestation. Ample food availability is necessary but does not guarantee household accessibility. Abstract: Background: In forest areas, reconciling strategies to halt deforestation and concerns to improve sustainable food supply and access is a great challenge to development planners and forest managers. This paper gathered evidence on the relationship between deforestation and food insecurity. The study was executed in Cameroon's forest areas which constitute 10% of the Congo basin forest - an area characterized by increasing deforestation and high levels of poverty and food insecurity (FIS). The objective was to understand the characteristics, prevalence and severity of household FIS as deforestation increases. The HFIAS 9-item questionnaire for measuring experience-based FIS was used for data collection and analysis. Results: At least one-third of households at all levels of deforestation were severely food insecure and more than half of the population suffered from moderate to severe FIS. Most (97%) households reported experiencing food scarcity due to lack of resources. Households in the least deforested zone were better off than those in moderate and most deforested zones by most of the FIS indicators, while differences between the moderately and the most deforested zones were less distinct. Overall, considering a range of food insecurity indicators, households in the most deforested zone were the worst off. Conclusion: Household FIS deteriorates with increasing deforestation and despite the generally favourable environmental conditions for food production, FIS was still high. This finding has major implications for development practitioners, land use planning, food security and conservation initiatives.